Current problems of economic integration : the problems of promoting and financing integration projects - United Nations Conference on Trade and Development (New York : United Nations, 1986)
This is a report of the meeting of secretariat of Economic Co-operation and Integration Groupings of developing countries and multi-lateral development finance institutions to examine the problems of promoting and financing integration projects
"TD/B/C.7/79"--T.p. verso.
"United Nations publication sales no. E.86.II.D.1"--T.p. verso.
Includes bibliographical references.
osc 30/01/2019
Loans
Keywords: International economic integration; Development banks; Developing countries